Diffusion in hydrogeology - Barker, John A. (Diffusion Fundamentals, 2007)
The field of hydrogeology is primarily concerned with the flow of water below the ground surface and with transport, normally of solutes and heat, within that water. Many disciplines have contributed to this endeavor which requires skills from across the spectrum of science, engineering and beyond. The diffusion equation describes not only solute transport but also the flow of water, via Darcy’s law. Of particular interest is transport in fractured rock where most of the flow is through the fractures while most of the storage is in the rock pores: a ‘double-porosity’ system. Hydrogeology remains a field that welcomes those who bring techniques from other areas of science to address problems as varied as water supply, radioactive waste disposal and geothermal energy.